2020
DOI: 10.9734/jpri/2020/v32i1330583
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Conventional Gastric Adenocarcinoma and EBV Associated Gastric Carcinoma

Abstract: Epstein Barr Virus (EBV or Human herpesvirus 4) belongs to the genus Lymphocryptoviridae, the gamma 1 subtype of the Subfamily Gamma herpes viridae and is one of the most common viruses in humans. It is present in all populations, infecting more than 95% of all individuals within the first four decades of life. In developing countries, infections occur very early in life with no specific characteristics other than the general symptoms of acute viremia. In developed countries however, the infection is usually d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that Epstein-Barr virus (EBV) is a ubiquitous oncogenic virus, which causes about 2% of cancers to occur by regulating the activities of a variety of host cells [ 24 ]. Early-life EBV infection can result in infectious mononucleosis, a self-limiting lymphoproliferative illness [ 25 ]. Huang et al believed that EBV infection was related to the development of human malignancies [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Epstein-Barr virus (EBV) is a ubiquitous oncogenic virus, which causes about 2% of cancers to occur by regulating the activities of a variety of host cells [ 24 ]. Early-life EBV infection can result in infectious mononucleosis, a self-limiting lymphoproliferative illness [ 25 ]. Huang et al believed that EBV infection was related to the development of human malignancies [ 26 ].…”
Section: Discussionmentioning
confidence: 99%